2017
DOI: 10.1159/000480414
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA FAL1 Promotes Cell Proliferation, Invasion and Epithelial-Mesenchymal Transition Through the PTEN/AKT Signaling Axis in Non-Small Cell Lung Cancer

Abstract: Background/Aims: Recently, long non-coding RNAs (lncRNAs) have been found to have many biological effects in different cancer stages. Several studies have revealed that focally amplified lncRNA on chromosome 1 (FAL1) regulates cancer progression via p21. However, the expression and mechanism of FAL1 in non-small cell lung cancer (NSCLC) still remain unclear. Methods: We detected the FAL1 level in NSCLC tissues and in established cell lines using quantitative real-time PCR and evaluated the clinical significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…Wang et al showed that over‐expression of ELF3 promoted cell proliferation and metastasis via PI3K/Akt and ERK signaling pathways in NSCLC . Pan et al demonstrated that lncRNA FAL1 induced cell proliferation, epithelial‐mesenchymal transition, and invasion via modulation of PTEN/AKT signaling pathway in NSCLC . Zhang et al provided evidences that Kctd20 stimulated the development of NSCLC by activating Fak/AKT pathway and related to poor OS of patients .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al showed that over‐expression of ELF3 promoted cell proliferation and metastasis via PI3K/Akt and ERK signaling pathways in NSCLC . Pan et al demonstrated that lncRNA FAL1 induced cell proliferation, epithelial‐mesenchymal transition, and invasion via modulation of PTEN/AKT signaling pathway in NSCLC . Zhang et al provided evidences that Kctd20 stimulated the development of NSCLC by activating Fak/AKT pathway and related to poor OS of patients .…”
Section: Discussionmentioning
confidence: 99%
“…Focally amplified lncRNA on chromosome 1 (FAL1), a new identified LncRNA located at 1q21.2, had been demonstrated to be up‐regulated and to promote development in several kinds of tumours, especially ovarian cancer . Pan et al reported that FAL1 was obviously overexpressed in NSCLC tissues compared with the adjacent normal tissues and promoted metastasis of NSCLC via the PTEN/AKT axis …”
Section: Main Molecular Mechanism Of Lncrna To Regulate the Metastasimentioning
confidence: 99%
“…In addition XLOC_008466, FAL1, and XIST were examined in NSCLC by Yang [38], Pan [39] and Wang, [40], respectively In their studies, these lncRNA function as an oncogene in NSCLC, which indicates them as a useful marker and potential therapeutic target.…”
Section: Lncrna In Lung Cancer Diagnosis and Tumor Typesmentioning
confidence: 99%